The Relationship Between Child Self-Regulation and Maternal and Child Weight Status - Baxter, Marlene (My University, 2024)
This study investigated the relationship between child self-regulation at preschool age and child and maternal weight status. It was carried out as part of the longitudinal mother-child study that has been conducted by the Early Nutrition and Health research group at the Institute of Biomedicine and Nutrition and Food Research Center of University of Turku. The final sample of this follow-up study consisted of 148 mothers and 148 children aged 5-6 years. Child’s self-regulation abilities were assessed by delay of gratification choice paradigm with food and non-food items as rewards and Behavior Rating Inventory of Executive Function 2 parent form that evaluates Executive Functioning (EF) skills. The weight status of mothers and children was defined based on Body Mass Index (BMI). Mothers were categorized to overweight (n = 95) and obese (n = 53) groups based on their prepregnancy BMI and children to normal weight (n = 109) and overweight/obese (n = 39) groups. In this study, no association was found between child’s weight status and their ability to delay gratification with food and non-food items as rewards. Children with normal weight and overweight/obesity did not differ in their EF skills. Children of mothers with prepregnancy obesity compared to those with overweight, delayed gratification less with food and non-food rewards and showed more difficulties in inhibition. The results suggest that maternal prepregnancy weight status is associated with child self-regulation skills at preschool age, whereas child weight status is not.
Keywords: Obesity, overweight, delay of gratification, executive functioning, self-regulation